2021
DOI: 10.1101/2021.05.26.445742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How many replicates to accurately estimate fish biodiversity using environmental DNA on coral reefs?

Abstract: Quantifying the diversity of species in rich tropical marine environments remains challenging. Environmental DNA (eDNA) metabarcoding is a promising tool to face this challenge through the filtering, amplification, and sequencing of DNA traces from water samples. However, the reliability of biodiversity detection from eDNA samples can be low in marine environments because eDNA density is low and certainly patchy in this vast, heterogenous and dynamic environment. So, the number of sampling replicates and filte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…However, our site-based and station-based accumulation curves do not reach plateaus suggesting that our sampling effort was not sufficient to exhaustively estimate fish biodiversity for each site (electronic supplementary material, analyses, figure S5) and station (electronic supplementary material, analyses, figure S6). Twenty-five replicates (so, 12 stations in case of field duplicates) could accurately estimate biodiversity regionally due to high local turnover [53]. A higher number of eDNA samples would be necessary here to reach MOTU accumulation per site and station.…”
Section: Discussionmentioning
confidence: 99%
“…However, our site-based and station-based accumulation curves do not reach plateaus suggesting that our sampling effort was not sufficient to exhaustively estimate fish biodiversity for each site (electronic supplementary material, analyses, figure S5) and station (electronic supplementary material, analyses, figure S6). Twenty-five replicates (so, 12 stations in case of field duplicates) could accurately estimate biodiversity regionally due to high local turnover [53]. A higher number of eDNA samples would be necessary here to reach MOTU accumulation per site and station.…”
Section: Discussionmentioning
confidence: 99%
“…However, replication quality and sampling effort may vary according to the studied environment because biotic and abiotic conditions can influence degradation, deposition and detection of eDNA (Stewart, 2019). For example in highly diverse tropical marine ecosystems where eDNA shedding and decay rates tend to be higher, partially due to higher water temperature (Jo et al, 2019), a study by Stauffer et al (2021) highlighted strong dissimilarity in species composition between filtration replicates (e.g., dissimilarity β jac mean = 0.729 ± 0.102 in the West Indian Ocean; β jac mean = 0.528 ± 0.146 in the Caribbean Sea, with a major contribution of the turnover component for both sampling areas) and required additional sampling efforts to ensure robust biodiversity estimates.…”
Section: Discussionmentioning
confidence: 99%
“…It further emphasises the need for incorporation of field replicates, as is recommended for other eDNA substrate types 36 . Studies of airborne eDNA monitoring of insects have not incorporated and contrasted field replicates 37,38 , however in studies on marine eDNA, a similar patchy distribution of DNA has been observed with paired field replicates not detecting the exact same community 39,40 . In the present study, we found no differences in the vertebrate composition between microhabitats, nor sampling sites.…”
Section: Discussionmentioning
confidence: 99%